The American revolution, 1775 - 1783 - Alden, John Richard (Harper, 1954)
Launching a new series of encyclopedias entitled The Wars of the United States, this panoramic reference comprises some 700 detailed mini-essays on battles, campaigns, skirmishes, raids, massacres, and sea fights, along with approximately 400 biographical sketches of the leading American, British